c-Abl-TWIST1 Epigenetically Dysregulate Inflammatory Responses during Mycobacterial Infection by Co-Regulating Bone Morphogenesis Protein and miR27a - Mahadik, Kasturi; Prakhar, Praveen; Rajmani, R. S.; Singh, Amit; Balaji, Kithiganahalli Narayanaswamy (Frontiers in Immunology, 2018)
Mycobacteria propelled modulation of host responses is of considerable interest in the face of emerging drug resistance. Although it is known that Abl tyrosine kinases affect entry and persistence of mycobacteria, mechanisms that couple c-Abl to proximal signaling pathways during immunity are poorly understood. Loss-of-function of c-Abl through Imatinib, in a mouse model of tuberculosis or RNA interference, identified bone morphogenesis protein (BMP) signaling as its cellular target. We demonstrate that c-Abl promotes mycobacterial survival through epigenetic modification brought about by KAT5-TWIST1 at Bmp loci. c-Abl-BMP signaling deregulated iNOS, aggravating the inflammatory balance. Interestingly, BMP signaling was observed to have far-reaching effects on host immunity, as it attenuated TLR3 pathway by engaging miR27a. Significantly, these events were largely mediated via WhiB3 and DosR/S/T but not SecA signaling pathway of mycobacteria. Our findings suggest molecular mechanisms of host pathways hijacked by mycobacteria and expand our understanding of c-Abl inhibitors in potentiating innate immune responses.